2019
DOI: 10.1371/journal.pone.0212609
|View full text |Cite
|
Sign up to set email alerts
|

An indirect debiasing method: Priming a target attribute reduces judgmental biases in likelihood estimations

Abstract: Understanding the underlying psychological process that leads to a bias is crucial for developing remedies to correct or reduce the bias. As one of the psychological processes that underlie judgmental biases, attribute substitution provides an explanation as to why people rely on heuristics and commit judgmental biases. Attribute substitution occurs when people make a judgment that requires the use of a target attribute, but make the judgment using a heuristic attribute that comes more readily to mind. This su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 68 publications
1
5
0
1
Order By: Relevance
“…Another avenue for future research relates to the gaps in the literature about the antecedents of cognitive biases like individual differences (such as gender) and emotions (such as such as apprehension, fear or anxiety) (Fagley et al , 2010). To reduce the bias, understanding the underlying psychological process is crucial (Lee, 2019). As decision-making is a complex activity that is influenced by many factors (Korhonen et al , 2018), cognitive biases' antecedents need to be analyzed.…”
Section: Conclusion and Discussion/implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another avenue for future research relates to the gaps in the literature about the antecedents of cognitive biases like individual differences (such as gender) and emotions (such as such as apprehension, fear or anxiety) (Fagley et al , 2010). To reduce the bias, understanding the underlying psychological process is crucial (Lee, 2019). As decision-making is a complex activity that is influenced by many factors (Korhonen et al , 2018), cognitive biases' antecedents need to be analyzed.…”
Section: Conclusion and Discussion/implicationsmentioning
confidence: 99%
“…The results of experiments showed that debiasing-training effects can improve decision-making. Lee (2019) explored the priming of a target attribute as an indirect debiasing method. After three experiments, it was demonstrated that judgmental biases reduced in likelihood estimations: ratio-bias and base-rate neglect when participants have enough cognitive resources.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors, however, that influence adult judgements on these problems. Relatively straightforward task manipulations that enhance the salience or relevance of the base rate information have led to an attenuation, elimination, or even a reversal of the BRN effect (Bago & De Neys, 2020; Case et al, 1999; Chun & Kruglanski, 2006; Hsee et al, 2019; Lee, 2019; Pennycook et al, 2014; Pennycook & Thompson, 2012; Wu & Emery, 2021). Similarly, manipulations that clarify the causal relation underlying the stereotypes in the case description increase belief-based responding on the task (Turpin et al, 2020).…”
mentioning
confidence: 99%
“…nos auxilia a ter a dimensão da velocidade com que os pesquisadores exploravam tal questão naquela época. empregada para reduzir o viés da taxa base (que consiste em ignorar a probabilidade envolvida na ocorrência de eventos), que se mostrou eficaz, consiste em apresentar palavras relacionadas com o atributo final da decisão em questão, tais como "probabilidade, proporção, percentual, possibilidade e chances"(Lee, 2019). Ainda que exposto de maneira rápida a esse estímulo (palavrasenviesado(Li & Cheung, 2020), uma vez que levam os requerentes a revisar e reestimar as suas decisões.…”
unclassified